Implementación de un sistema contable y aplicación de indicadores financieros en la empresa Bambinos pañalera de la ciudad de Loja. Periodo 01 de mayo al 30 de junio del 2016 - Camacho Maurad, Geomara Izebet (2017)
The thesis work entitled "IMPLEMENTATION OF A ACCOUNTING SYSTEM AND APPLICATION OF FINANCIAL INDICATORS IN THE COMPANY BAMBINOS PAÑALERA DE LA CIUDAD DE LOJA. PERIOD 01 MAY TO JUNE 30, 2016 " is aimed firstly at proposing an accounting system based on the Permanent Inventory method, allowing its owner to obtain quality information and to know the real economic - financial situation of the company. And secondly, it will serve as an indispensable requirement in compliance with Art. 129 of the REGULATIONS OF ACADEMIC REGIME OF THE NATIONAL UNIVERSITY OF LOJA which requires, through its pertinent part, its realization, to obtain the Degree of Engineering in Accounting and Auditing. During the development and execution of the general objective, the specific objectives that were established were: To carry out an inventory of goods, values, rights and obligations that allow to know in general the patrimony with which the company currently has. Elaborate a Plan and Manual of accounts that facilitates the identification and personification of the operations generated in the company and serves as a guide in the proper registration of the accounting accounts. Also, Apply the Permanent Account System that allows to register and properly control the merchandize account. Develop an Accounting Process to record in an orderly and systematic way the daily operations of the company and to know the economic and financial results at the end of the study period. And finally Apply Financial Indicators that help to evaluate the performance and facilitate to know the level of liquidity, activity, profitability and indebtedness of the business. Finally, the Conclusions and Recommendations of all the thesis work are presented so that the Owner Manager considers them as an option in taking corrective measures that help the progress of the business. It is worth mentioning that among the aforementioned conclusions emphasis is given to the application of the Financial Indicators where their results showed mainly that the company "BAMBINOS PAÑALERA" owns a rotation of Inventories very low of 0,10 times in a period of 2 months, which Has resulted in a very high LOSS OF THE YEAR ($ 2,313.08) during the study period. Therefore, it was necessary to suggest or recommend that measures be taken to control the acquisition of merchandise, establishing purchasing limits and improving sales strategies by increasing publicity or by making promotions and discounts.